DEVELOPMENT OF COLLABORATIVE MATHEMATICS LEARNING MODEL GOGAR INTEGRATED WITH ETNOMATHEMATICS TO IMPROVE REASONING ABILITY - M.Pd., Dr. Rick Hunter Simanungkalit (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2026)
The purpose of this study was to determine: (1) the quality of the Collaborative Mathematics Learning Model GoGAR integrated with Ethnomathematics that was developed, and (2) to determine the increase in students' mathematical reasoning abilities with the Collaborative Mathematics Learning Model GoGAR integrated with Ethnomathematics. This study is a development research using the Thiagarajan development model, namely the modified 4D model (Define, Design, Develop, and Disseminate). In addition to the model, learning tools were also developed to support the implementation of the model in the form of RPP, LKS, student books, and instruments to test students' mathematical reasoning abilities. The research instruments were in the form of: (a) model validation sheets and learning tools; (b) observation sheets to see the teacher's ability to manage learning and student activities; (c) research questionnaires to see students' responses to the learning model that was developed. The results of the data analysis showed that the Collaborative Mathematics Learning Model GoGAR integrated with Ethnomathematics met the criteria of valid, practical, and effective. There was an increase in students' mathematical reasoning abilities using the developed learning model.